"Emasculation nation has arrived": sexism rearticulated in online responses to Lose the Lads' Mags campaign. Issue 3 (3rd May 2016) - García-Favaro, Laura; Gill, Rosalind
Abstract: In the spring of 2013 a British feminist campaign sought to have men's magazines, such as Zoo, Nuts, and Loaded, removed from the shelves of major retailers, arguing that they are sexist and objectify women. The campaign—known as Lose the Lads' Mags (LTLM)—received extensive media coverage and was the topic of considerable public debate. Working with a data corpus comprising 5, 140 reader comments posted on news websites in response to reporting of LTLM, this paper explores the repeated focus on men and masculinity as "attacked, " "under threat, " "victimised, " or "demonised" in what is depicted as a sinister new gender order. Drawing on a poststructuralist feminist discursive analysis, we show how these broad claims are underpinned by four interpretative repertoires that centre around: (i) gendered double standards; (ii) male (hetero)sexuality under threat; (iii) the war on the "normal bloke"; and (iv) the notion of feminism as unconcerned with equality but rather "out to get men." This paper contributes to an understanding of (online) popular misogyny and changing modes of sexism.